The Effect Of Customer Focus Strategy, Corporate Entrepreneurship And Organizational Innovation On Sustainable Competitive Advantage - Eryco Muhdaliha; Jemmy Jemmy; Panca Maulana Firdaus; Dadet Sugiarto; Heru Nugroho (Maneggio, 2024)
This research intends to investigate the impact of customer focus strategy, corporate entrepreneurship, and organizational innovation on long-term competitive edge. In the current fast-paced and highly competitive business landscape, achieving a sustainable competitive advantage that organizations constantly evolve and drive innovation. A customer focus strategy emphasizes understanding and meeting customer needs, which enhances customer satisfaction and loyalty. Corporate entrepreneurship fosters a culture of intrapreneurship, empowering employees to drive innovation and strategic growth. Organizational innovation, both technological and non-technological, serves as a catalyst for improving processes, products, and services. This research employs a numerical method, utilizing survey data from selected organizations and analyzing the bonds between variables applying Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings are expected to provide insights into how strategic capabilities, such as knowledge management, social capital integration, and organizational agility, mediate the bonds between these strategies and sustainable market dominance. This research adds to the literature by highlighting the importance of integrating customer focus, entrepreneurship, and innovation to achieve long-term organizational success in a rapidly evolving market landscape.